Voters of Populist Parties and Support for Reforms of Representative Democracy in Belgium - van Dijk, Lisa; Legein, Thomas; Pilet, Jean-Benoit; Marien, Sofie (Politics of the Low Countries, 2025)
Recently, studies have burgeoned on the link between populism and demands for democratic reforms. In particular, scholars have been debating the link between populist citizens or voters and support for referendums. In this article, we examine voters of populist parties (Vlaams Belang (VB) and Parti du Travail de Belgique-Partij van de Arbeid (PTB-PVDA)) in Belgium in 2019 and we look at their attitudes towards various types of democratic reforms. We find that voters of populist parties differ from the non-populist electorate in their support for different kinds of reforms of representative democracy. Voters of VB and PTB-PVDA have in common stronger demands for limiting politicians’ prerogatives, for introducing binding referendums and for participatory budgeting. While Vlaams Belang voters are not significantly different from the non-populist electorate on advisory referendums, citizens’ forums or technocratic reform, PVDA-PTB voters seem more enthusiastic.